Peran Kepemimpinan Transformational dan Partisipasi Tenaga Kesehatan Terhadap Peningkatan Komitmen Implementasi Keselamatan dan Kesehatan Kerja (K3) di RSUD Mardi Waluyo Kota Blitar - Ardhi Syamsarifin (Poltekkes Kemenkes Semarang, 2022)
Background: The leader is a real symbol of power. The success of an organization in achieving its goals is largely determined by the ability of its leaders. Every workforce is entitled to protection for occupational safety and health (K3) in doing work. The purpose of the study is to analyze the influence between transformational leadership and health worker participation on the improvement of K3 implementation commitment at Mardi Waluyo Blitar Hospital.Methods: Design observational research with a cross-sectional approach. The population of all health workers in Mardi Waluyo Hospital in Blitar City amounted to 834 people, while sampling techniques were conducted by probability sampling technique using Proportionate Stratified Random Sampling. The samples were obtained from Kerjcie and Morgan's table of 260 people with total sampling techniques. Independent variables are transformational leadership and the role of healthcare workers. The dependent variable is the K3 implementation commitment. The analyses used are univariate, bivariate and multivariate.Results: The results showed that there was a co-influence between transformational leadership (p=0.000) and health worker participation (p=0.021) on the increased commitment to K3 implementation at Mardi Waluyo Blitar Hospital. Multivariate analysis shows the most dominant variables are transformational leadership with significance levels p=0.000 and B=0.274.Conclusions: By participating in the research, it is expected that respondents can improve the quality of health services in hospitals by improving the implementation of K3 as a guideline or standard in providing quality health services and prioritizing patient safety and preventing occupational accidents in health workers.